Autonomie de l’apprenant et préparation à la médiation interculturelle - Wilczyńska, Weronika (Neophilologica, 2006)
In didactics interculturalism is usually perceived from the perspective of the relations between certain communities, which blurs the individual level of approaching and handling the intercultural problems. In case of such problems Weronika Wilczyńska suggests assuming the perspective of a student, not the one of a group represented by this student. This approach pivots on the idea of the bilingual, multilingual or multicultural identity as the one characteristic of a bilingual or multilingual person. Basing on this identity such a person can develop cultural sensitivity that allows them to do more than just perceive superficial differences. Thanks to this sensitivity such a person shall be able to interpret the whole of discursive practices as an important determinant of their partner identity.